(untitled) - Mahabub Basha S, Aditi Priya Singh , Dr. Mohammed Rafi , Mrs. Ibha Rani , Dr. N Mukund Sharma (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Predicting the Pharmaceutical stocks along with Nifty index is possibly one of the very toughest exercises in Indian Capital Markets. The present study focuses on Short & Long term dynamics of the Pharmaceutical industry in Indian capital market. The Pharmaceutical sector along with Nifty Index Regular closing monitory value are a sample to the analysis between June 2015 and June 2020. In the paper, ADF test is embarked to examine immovability of data and is evident that it is un-movable at initial difference level. The co-integration test of Johansen is applied to assess long-term balance of Nifty Index analysis with the pharmaceutical sector and to define the co-integration of the variables. Granger causality test is used to regulate causal & short-term relationship of the variables with the corresponding bidirectional casualties amidst them.